2016
DOI: 10.1017/s1368980016001373
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of sugar-sweetened beverages and its association with overweight among young children from China

Abstract: Objective: To fully understand the sugar-sweetened beverage (SSB) consumption status among Chinese young children and to explore its association with weight gain. Design: In this cross-sectional study, data on sociodemographic characteristics, SSB intake and weight/height were collected by means of face-to-face interviews. The intake of SSB among young Chinese children in relation to their age, different characteristics and types of SSB consumed is described, and the association between SSB intake and BMI-for-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 33 publications
2
36
1
2
Order By: Relevance
“…A previous study demonstrated that most parents held the misconception that milk beverage had the same nutritional value as milk for children and adolescents and can be used as long-term substitutes for milk [38], thereby resulting in the high consumption of milk beverage. Moreover, the consumption proportions of ≥3 times/week among the four surveyed sugar-sweetened beverages (SSBs) was consistent with results of one previous study, which showed that vegetable/fruit-flavoured drinks and tea beverage had become the leading SSBs in China [39]. With increasing studies and rapid spread of mass media, the public has improved the awareness of the high sugar content and hazards of carbonated SSBs (CSSBs) [40,41].…”
Section: Discussionsupporting
confidence: 85%
“…A previous study demonstrated that most parents held the misconception that milk beverage had the same nutritional value as milk for children and adolescents and can be used as long-term substitutes for milk [38], thereby resulting in the high consumption of milk beverage. Moreover, the consumption proportions of ≥3 times/week among the four surveyed sugar-sweetened beverages (SSBs) was consistent with results of one previous study, which showed that vegetable/fruit-flavoured drinks and tea beverage had become the leading SSBs in China [39]. With increasing studies and rapid spread of mass media, the public has improved the awareness of the high sugar content and hazards of carbonated SSBs (CSSBs) [40,41].…”
Section: Discussionsupporting
confidence: 85%
“…In our present findings, we found a trend of higher volumes of SSB consumption in older children of preschool age (5 years v. 18 months). In our study, 98 % of participants were consuming SSB by 5 years of age, and this percentage is higher than the 80•5 % children in China consuming SSB by 3-7 years of age (14) . This observation is in line with a survey conducted in 800 Singaporean children in 2009 examining their beverage consumption habits.…”
Section: Discussioncontrasting
confidence: 55%
“…These observations concur with the few existing cross-sectional studies (34)(35)(36) and one prospective study (11) in children of a similar age range. These studies have all used body weight measures (BMI or BMI z score) as a main outcome and have defined the overweight/obesity statuses of children (11,14,34,35) , but none examined SSB intake with skinfold measures. SSF thickness (usually biceps, triceps, supra-iliac and subscapular) has been shown to be a useful supplementary measure widely used to assess body fatness in children (37) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesogenic behaviours, including high screen time [1,2], consumption of sugar sweetened beverages (SSBs) [3,4] and lack of sleep [5,6] have become more prevalent in children and adolescents in recent years. In addition to age, socioeconomic status (SES), sex [7,8] and parental education [7,9], the family environment has a major influence on children's and adolescent's behaviour [10].…”
Section: Introductionmentioning
confidence: 99%